Efficacy of light curing sources and different dentin bonding agents on microleakage of class II resin composite restorations - M Barekatein; P Mirzakoochaky (Isfahan University of Medical Sciences, 2007)
Introduction: By increase of esthetic demand, application of resin composite as a posterior restoration is greater than before. Microleakage and post operative sensitivity are two challenges to the success of this filling material. To overcome these, the best selection of dentin bonding system and light curing units are important. This study evaluated the two above mentioned factors.Methods and Materials: In this experimental study class II cavities were prepared in both mesial and distal side of 30 healthy third molar teeth, and the samples randomly divided into 4 groups. Each group restored by use of one of these bonding system: total etch (Excite) or self etch (SE Bond) and one of light curing units: QTH or LED, and a similar restorative composite. After thermocycling, sealing and immersing the samples in dye, they sectioned and evaluated by steriomicroscope and analyzed by Mann-Whitney test.Results: LED light curing unit and self etch bonding agent had best result in controlling microleakage.Conclusion: LED depth of cure is more than that of QTH and the efficacy of self etch primer to infiltration etched dentin is greeter than total etch dentin bonding agents, because they do not dehydrate dentin and do not collapse collagen fibers.Key words: Microleakage, Self etch primer, Total etch, LED, QTH